GOVERNMENTAL INNOVATION OF SABANG CITY IN SUPPORTING 12 YEARS MANDATORY POLICY - Iin Nurhalizha (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2019)
Abstract: The lack of provision of learning tools and facilities both from parents and from the government is a serious problem in the implementation of education. The implementation of regional autonomy by the laws and regulations is very important in the distribution of education funds to succeed in the 12-year compulsory education policy. One government that has contributed to the attention of the Human Resources (HR) of the community is the City Government (Pemko) Sabang. Sabang City Government provides educational funding assistance in the Jak geutanyo saving campaign (Let's Save) according to the needs of the community. This paper aims to describe the equitable distribution of Sabang municipal funds for the success of the 12-year compulsory education policy. This research uses a descriptive qualitative approach. The research subjects were the Sabang City government, the community, and Sabang City students. The object of the study is the policy of the Pemko Sabang in the distribution of education funds. Data collection techniques used were observation, interviews, documentation, and literature study. The data analysis technique used is descriptive analysis technique. The results of the study found that the distribution of education funds for the Sabang City Government obtained from the City Revenue and Expenditure Budget (APBK) had been met compared to other regions. The financial assistance is given in one school year. To get these funds, students must meet the general criteria, namely; domiciled in the city of Sabang, and have been educated at least 11 months in one of these schools. The success of this program can be seen in the level of satisfaction of the community who expect such assistance because it is very helpful in all educational needs, also in equal distribution of education (12-year compulsory education policy), and can create prosperity for the people of Sabang City.